ATRT-08. A PHASE II STUDY OF CONTINUOUS LOW DOSE PANOBINOSTAT IN PAEDIATRIC PATIENTS WITH MALIGNANT RHABDOID TUMORS/ATYPICAL TERATOID RHABDOID TUMORS. (4th December 2020) - Wood, Paul; Desai, Jayesh; Waldeck, Kelly; Cain, Jason; Gottardo, Nick; Strong, Robyn; Kinross, Kathryn; Carr, Michelle; Jones, Janelle; Wong, Lily; Ziegler, David; Hansford, Jordan; et al.
Abstract: BACKGROUND: Panobinostat treatment has been shown to terminally differentiate malignant rhabdoid tumor (MRT)/atypical teratoid rhabdoid tumors (ATRT) in pre-clinical models. This is an open label, phase II study of panobinostat in patients with newly diagnosed or relapsed MRT/ATRT. AIMS: To assess the anti-tumor activity of low dose, continuous panobinostat, its associated toxicities, the biological activity of low dose panobinostat by measuring histone acetylation status in peripheral mononuclear cells (PMNC), and markers of differentiation in fresh tumor tissue specimens. METHODS: Following cycles of induction and consolidation chemotherapy and/or radiation treatment, patients were enrolled and commenced on panobinostat as a continuous daily oral dose starting at 10mg/m 2 following a three-week wash out period between therapies. Real-time acetylation status, measuring acetylated H4 on PMNC, was performed to determine the pharmacodynamics of panobinostat. Patients were monitored for drug toxicities with the possibility of dose reductions in decrements of 2mg/m 2 . RESULTS: Six patients with newly diagnosed ATRT/MRT and one patient with relapsed MRT have been enrolled to date. The average age at enrollment was 2.5 years. Currently, six patients (85.7%) remain on study with a mean treatment duration of 170 days (range 44–327 days). One patient was removed from study at day 44 due to disease progression. The main dose-limiting toxicity observed to date has been myelosuppression. Panobinostat, at a dose of 10mg/m 2, caused significant acetylation of H4 in PMNC. CONCLUSIONS: Treatment with panobinostat appears to be well tolerated in infants with MRT/ATRT, with successful real-time pharmacodynamic assessment of H4 acetylation.